The Effect of Small-Sided Games on the Passing Skills of Futsal Players at the Bengkulu Futsal Female (BFF) Club in Bengkulu City - Intan Ulandari; Megi Personi; Martiani Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of small-sided games on the passing skills of futsal athletes at the Bengkulu Futsal Female (BFF) club in Bengkulu City. This study employed an experimental method using a one-group pretest-posttest design. The study population consisted of 20 participants. This study used total sampling, with a sample size of 20 players. This can be seen from the average improvement after 16 treatment sessions, as indicated by the pre-test and post-test data. The pre-test had a highest score of 6, a lowest score of 3, and an average of 4.65. The post-test had a highest score of 9, a lowest score of 3, and an average of 6.3. The pre-test score of 4.65 increased to 6.3 in the post-test. The analysis results showed a t-value of 17.27, indicating that the influence of small-sided games on the passing skills of Futsal athletes at the Bengkulu Futsal Female (BFF) club in Bengkulu City is statistically significant. It can be concluded that there is an influence of small-sided game training on the passing skills of Futsal athletes at the Bengkulu Futsal Female (BFF) club in Bengkulu City.